Impacts of GFP-FoxP3+ regulatory T cells on lupus hallmarks differ by genetic background and type of GFP knock-in. (18th August 2019) - Chang, Soog-Hee; Kim, Tae-Joo; Kim, Yongbaek; Han, Seung Seok; Lee, Sun-Kyung; Sim, Ji Hyun; Kim, Young-Joo; Lee, Se Jeong; Rhyu, Im Joo; Nam, Ki-Hoan; Mohan, Chandra; Kim, Hang-Rae
Abstract: FoxP3 reporter mice expressing green fluorescence protein (GFP) have been used as a very convenient tool to investigate the impact of regulatory T (Treg) cells on pathogenesis in autoimmune diseases. Here, we found that GFP-FoxP3 + knock-in (KI) mice showed alterations in the production of anti-nuclear autoantibodies (ANAs) and nephritis with different extent, depending on the presence or absence of lupus susceptibility gene locus 1 ( Sle1 ) and KI method: contrasting with B6. Sle1 .fGFP-FoxP3 mice, expressing GFP via N-terminal insertion, B6. Sle1 .iGFP-FoxP3, expressing GFP via bicistronic internal ribosome entry site-driven promotion, exhibited significantly lower penetrance of serum ANA, comparing to control B6. Sle1 mice. Moreover, B6.Sle1 .GFP-FoxP3 + mice reduced the Sle1 -induced splenomegaly and B-cell expansion independently of the KI method employed, mainly by reducing the numbers of transitional 1 (T1) B cells and CD21 – CD23 – B cells, including plasmablasts and plasma cells. The absolute numbers of both splenic CD4 + T cells and Treg cells from B6. Sle1 .GFP-FoxP3 KI mice were significantly reduced but their proportion was not changed, compared to B6. Sle1 mice. Although the glomerular basement membranes were thickened in both B6. Sle1 and B6. Sle1 .iGFP-FoxP3 mice, they were thinner in B6. Sle1 .fGFP-FoxP3 mice. The latter mice expressed more nephrophilic autoantibodies and deposited more complement component 3 in glomeruli compared to B6.iGFP-FoxP3 mice. FoxP3 + Treg cells may modulate B-cell tolerance in lupus-prone B6. Sle1 mice, presumably by modulating pathogenic, nephrophilic autoantibody production and nephritis.